PENGARUH PERCEIVED QUALITY, PERCEIVED USEFULNESS, DAN PERCEIVED EASE OF USE TERHADAP KEPUASAN PELANGGAN E-COMMERCE SHOPEE DI KOTA SURABAYA - Imanuel Karinda, Ivan (Universitas Halu Oleo, 2024)
Abstract This study aims to determine and analyze the effect of both simultaneously and partially the variables of perceived quality, perceived usefulness, and perceived ease of use on Shopee e-commerce customer satisfaction in Surabaya City. This research is an associative research using a quantitative approach. The sampling techniques used in this study were purposive sampling techniques and quota sampling with a total sample of 100 people. The data analysis technique used in this study is multiple linear regression analysis using SPSS version 29. The results of this study show that perceived quality, perceived usefulness, and perceived ease of use both simultaneously and partially have a significant effect on Shopee e-commerce customer satisfaction in Surabaya City. Keywords: perceived quality; perceived usefulness; perceived ease of use; customer satisfaction; e-commerce.